Endovascular conversion into aorto-uniiliac configuration of acute failed endovascular aneurysm repair is associated with better one-year survival rates compared to open conversion. Issue 3 (June 2017) - Prusa, Alexander M.; Wibmer, Andreas G.; Nolz, Richard; Schoder, Maria; Teufelsbauer, Harald
Abstract: Background: Open conversions (OC) due to failed endovascular repair of infrarenal abdominal aortic aneurysms (EVAR) are technically demanding because of preexisting prostheses and advanced aortic disease. This study evaluates the feasibility and outcomes of aorto-uniiliac endografting (AUI) as an alternative treatment option in acute failed EVAR. Methods: From March 1995 through February 2012, 26 patients underwent acute conversion of failed EVAR at our tertiary care university center. All data were prospectively entered in our institutional database. Outcomes included 30-day or in-hospital mortality, postoperative complications, and mid-term survival. Results: During the investigation period, a total of 692 patients received EVAR at our institution, while five of the 26 patients with acute conversion (19.2%) had an initial EVAR at an outlying institution and were referred for treatment. Therefore, our estimated institutional rate of acute conversions was 3% (21 of 692 EVAR). OC were performed in 14 patients (53.8%), while 12 patients underwent AUI (46.2%). An average time of 20.3 months (median: 18.6; interquartile range Q1–Q3: 0.0–38.6) elapsed between the initial EVAR and the acute conversion. All acute AUI conversion procedures were completed successfully. The 30-day mortality following acute conversions was 42.3% and since the use of AUI, it could be reduced to 33.3%. Kaplan–Meier estimates revealed a survival advantage for AUI at one year (p = 0.046), but the benefit was lost by mid-term follow-up (p = 0.103). Conclusions: AUI for the treatment of acute failed EVAR represents a feasible and less invasive alternative to OC, and is associated with better one-year survival rates.